Індустрія 4.0 і формування ланцюгів (мереж) створення цінності на основі цифрових платформ - Липов, В.В. (Вісник економічної науки України, 2024)
В статті досліджено особливості використання платформної моделі як інструменту розширення можливостей побудови ланцюгів (мереж) створення цінності у сфері виробництва і підвищення ефективності взаємодії учасників виробничого процесу. Вони розглядаються як перспективний напрям посилення обороноспроможності України, забезпечення повоєнного відновлення і розвитку національної економіки, отримання конкурентних переваг та мінімізації негативних наслідків військової агресії. Представлено відмінності платформ цифрового досвіду і цифрового виробництва (промислових цифрових платформ). Розкрито місце і роль у забезпеченні виробничого процесу організаційних та трансакційних промислових цифрових платформ. The article examines the peculiarities of using a platform model as a tool for expanding the possibilities of building chains (networks) to create value in the production field and to increase the efficiency of interaction of participants in the production process. They are regarded as a promising direction for enhancing Ukraine’s defense, ensuring the post-war restoration and development of the national economy, obtaining competitive advantages, and minimizing the negative consequences of military aggression. Differences of digital experience and digital production platforms (industrial digital platforms) are presented. It is shown that unlike digital experience platforms that provide consumer interaction with each other and manufacturers of a product or service, industrial digital platforms create the ability to combine into a single ecosystem of contractors at different stages of production process. This is ensured both within the hierarchical structure (Industry 4.0) and the form of horizontal interaction of independent producers of individual components of the final product. The place and role in providing the production process of organizational and transactional industrial digital platforms are revealed. In the case of organizational industrial digital platforms, the core of digital platforms turns over the whole set of tasks for the organization of development, manufacture, market promotion, and after-sales product maintenance. In the case of transactional, the core of digital platforms acts as a mediator between the customer and the provider of production services. The latter may look for the components of the final product or rent equipment for its manufacture. It is shown that industrial digital platforms are capable of combining in the chains (networks) of creating the value of initiators of innovative solutions, developers of relevant technologies, design of a product or service, manufacturers of components of the final product, performers of logistics, marketing, after-sales support at all stages of life cycle.